Effect of Alumina Nanocoating on Thermal Stability of Y3Al5O12: Ce Phosphor - Chen, L.; Li, X.; Feng, W.; Tao, C.; Li, W. (Asian Journal of Chemistry, 2011)
Al2O3 film was successfully coated on the surface of YAG: Ce phosphor. The microscopic structure and thermal stability of Al2O3-coated phosphor were investigated. The results show that a smooth and uniform alumina nanocoating was formed on the surface of YAG: Ce phosphor particles, which revealed the formation of YAG: Ce-Al2O3 core-shell structure. The optical properties of Al2O3coated phosphor have shown that the luminescent intensity of Al2O3-coated YAG: Ce phosphor decreases slightly. But the thermal stability became better and the resistant light decay has been improved ca. 20 %.